Respon Pertumbuhan Bibit Kopi Arabika (Coffea arabica L.) terhadap Berbagai Jenis Media Tanam dan Dosis Pupuk Urea - SALSABILA FAADHILAH; I WAYAN WIRAATMAJA; I NYOMAN GEDE ASTAWA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2021)
Arabica Coffea Seed (Coffea Arabica L.) Growth Responses to Various Type of Planting Media and Urea Fertilization Dosage Arabica coffea is a type of coffee that has greater fruit characteristics and tastes better compared to robusta coffee so this commodity has the prospect of increasing the country's foreign exchange. To obtain quality crops, in the production process must be cultivated stages of good cultivation. To achieve this, cultivation techniques related to factors that affect the growth of arabica coffee seeds, namely planting media and urea fertilizer dosage. This study aims to find out the response of arabica coffee seedlings growth to various types of planting media and doses of urea fertilizer. This study used a Randomized Group Design (RAK) with two factors. The first factor is the type of planting media namely top soil (M1), top soil: sand (M2), top soil: cow manure (M3), the second factor is the dose of urea fertilizer namely control (N0), 0.5 g / polybag (N1), 1 g / polybag (N2), 1.5 g / polybag (N3). The results showed an interaction between the type of planting media and the dose of urea fertilizer against the variable leaf dry weight. Combination of top soil and sand with a dose of urea fertilizer 1.5 g / polybag gives the largest leaf dry weight of 6.20 g.